Peculiarities of plasma fluctuations during RF heating in Uragan-3M torsatron by means of two alfven waves - Pavlichenko, O.S.; Skibenko, A.I.; Volkov, E.D.; Berezhniy, V.L.; Ocheretenko, V.L.; Konovalov, V.G.; Kulaga, A.Ye.; Litvinov, A.P.; Pinos, I.B.; Prokopenko, A.V.; Shapoval, A.N.; Shvets, O.M.; et al. (Вопросы атомной науки и техники, 2005)
Three wave interaction has been observed in experiments on Uragan-3M torsatron. Two RF antennas with frequencies Ω1 and Ω2 were used simultaneously for plasma production and heating. Plasma was probed by microwaves, these allowed to study reflection of microwaves at almost whole plasma radius. Spectral analysis of reflected microwaves showed an existence of plasma density fluctuation with frequency Ω1 – Ω2. The suppression of plasma low frequencies was observed, when the plasma oscillation with Ω1 – Ω2 frequency has appeared. Microwaves probing of these fluctuations is the useful tool for studies of their influence on plasma behavior and possibly RF power absorption profile. Трьоххвильова взаємодія спостерігалась в експериментах на торсатроні Ураган-3М. Дві ВЧ антени з частотами Ω1 і Ω2 одночасно використовувались для створення і нагріву плазми, яка зондувалась мікрохвилями, місце відбиття яких перекривало майже весь радіус. При спектральному аналізі відбитих НВЧ сигналів виявлені флуктуації густини плазми з частотою Ω1 – Ω2. При появі коливань з частотою Ω1 – Ω2 спостерігалось пригнічення НЧ флуктуацій. Мікрохвильове зондування є корисним засобом для вивчення їх впливу на поведінку плазми та, можливо, для відтворення профілю поглинання ВЧ потужності. Трехволновое взаимодействие наблюдалось в экспериментах на торсатроне Ураган-3М. Две ВЧ антенны с частотами Ω1 и Ω2 одновременно использовались для создания и нагрева плазмы, которая зондировалась микроволнами, место отражения которых перекрывало почти весь радиус. При спектральном анализе отраженных СВЧ сигналов обнаружены флуктуации плотности плазмы с частотой Ω1 – Ω2. При появлении колебаний на частоте Ω1 – Ω2 наблюдалось подавление НЧ флуктуаций. Микроволновое зондирование является полезным средством для изучения их влияния на поведение плазмы и, возможно, для воссоздания профиля поглощения ВЧ мощности.